2022
DOI: 10.1155/2022/2791874
|View full text |Cite|
|
Sign up to set email alerts
|

Antihypertensive Activity in High Salt-Induced Hypertensive Rats and LC-MS/MS-Based Phytochemical Profiling of Melia azedarach L. (Meliaceae) Leaves

Abstract: Melia azedarach L. leaves have been traditionally used but not scientifically evaluated for antihypertensive activity. The focus of the present work was to carry out the detailed phytochemical profiling and antihypertensive potential of methanolic extract and subsequent fractions of this plant. The tandem mass spectrometry-based phytochemical profiling of M. azedarach extract (Ma.Cr) and fractions was determined in negative ionization mode while molecular networking was executed using the Global Natural Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Liquid chromatography-mass spectrometry (LC-MS) is a versatile and powerful analytical technique widely used for the identification and quantification of polyphenols from various plant extracts. Polyphenols are a diverse group of compounds with variable polarities and structures, making LC-MS an ideal choice due to its ability to separate, detect and analyze complex mixtures [63]. Our results are in agreement with the findings of [62], who reported that ethyl acetate extract of C. colocynthis roots showed the presence of ferulic acid and caffeic acid as major phenolic acids, followed by p-coumaric acid and vanillic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Liquid chromatography-mass spectrometry (LC-MS) is a versatile and powerful analytical technique widely used for the identification and quantification of polyphenols from various plant extracts. Polyphenols are a diverse group of compounds with variable polarities and structures, making LC-MS an ideal choice due to its ability to separate, detect and analyze complex mixtures [63]. Our results are in agreement with the findings of [62], who reported that ethyl acetate extract of C. colocynthis roots showed the presence of ferulic acid and caffeic acid as major phenolic acids, followed by p-coumaric acid and vanillic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Roseoside (36) was identified as a fatty acyl glycoside. Some typical fragmentation patterns were distinctive for the tentative identification of flavonoid glycoside showing galactose (162), rhamnose (146), and glucose (162) for O-glycosides [21]. Moieties such as 60, 90, and 120 were characteristic of C-glycosides [22].…”
Section: Total Phenolic Contentsmentioning
confidence: 99%
“…The LC-MS/MS analysis of the extract and various fractions was performed according to the procedure mentioned in Bashir et al (2021) with modifications where required using negative ion mode [21]. Briefly, samples of methanolic extract of G. velutinum and fractions were prepared by dissolving in HPLC grade methanol at a concentration of 1 mg/mL.…”
Section: Lc-ms/ms-based Metabolomic Profilingmentioning
confidence: 99%
“…Several medications are currently being used in the management of hypertension, including calcium channel blockers, beta-blockers, angiotensin converting enzyme (ACE) inhibitors, and diuretics. 2,3 Overall, the management of hypertension is complex whether through conventional medications or herbal remedies. Healthcare professionals must carefully consider the individual patient's needs, preferences, and health status when determining the most appropriate treatment approach and addressing any potential complications or clinical problems that may arise.…”
Section: Introductionmentioning
confidence: 99%